Antibody‐mediated neutralization of IL11 signalling reduces ERK activation and cardiac fibrosis in a mouse model of severe pressure overload. (18th January 2021) - Lim, Wei‐Wen; Corden, Ben; Ye, Lei; Viswanathan, Sivakumar; Widjaja, Anissa A.; Xie, Chen; Su, Liping; Tee, Nicole G. Z.; Schafer, Sebastian; Cook, Stuart A.
Abstract: Interleukin‐11 (IL11) is important for fibroblast‐to‐myofibroblast transformations. Here, we examined the signalling and phenotypic effects of inhibiting IL11 signalling using neutralizing antibodies against IL11 or its cognate receptor (IL11RA) in a mouse model of acute and severe pressure overload. C57BL/6J mice underwent ascending aortic constriction (AAC) surgery and were randomized to anti‐IL11, anti‐IL11RA, or isotype control antibodies (20 mg/kg, bi‐weekly for 2 weeks). AAC surgery induced the expression of IL11, IL11RA and extracellular matrix (ECM) genes that was associated with cardiac hypertrophy and aortic remodelling. Inhibition of IL11 signalling reduced AAC‐induced cardiac fibrosis and ECM gene expression as well as ERK1/2 phosphorylation but had no effect on cardiac hypertrophy. STAT3 was phosphorylated in the hearts of AAC‐treated mice but this was unrelated to IL11 activity, which we confirmed in mouse cardiac fibroblasts in vitro. These data highlight that blocking IL11 signalling reduces cardiac fibrosis due to severe pressure overload and suggests ERK, but not STAT3, activity as the relevant underlying signalling pathway. Abstract : Neutralizing IL11 signalling with anti‐cytokine or anti‐receptor antibodies reduces cardiac fibrosis via inhibition of ERK activation.